Experimental arts in postwar Japan : moments of encounter, engagement, and imagined return - Sas, Miryam (Harvard East Asian monographs ;, 2011)
In the years of rapid economic growth following the protest movements of the 1960s, artists and intellectuals in Japan searched for a means of direct impact on the whirlwind of historical and cultural transformations of their time. Yet while the artists often called for such "direct" encounter, their works complicate this ideal with practices of interruption, self-reflexive mimesis, and temporal discontinuity. In an era known for idealism and activism, some of the most cherished ideals--intimacy between subjects, authenticity, a sense of home--are limitlessly desired yet always just out of reach. In this book, Miryam Sas explores the theoretical and cultural implications of experimental arts in a range of media. Casting light on important moments in the arts from the 1960s to the early 1980s, this study focuses first on underground (post-shingeki) theater and then on related works of experimental film and video, buto dance and photography. Emphasizing the complex and sophisticated theoretical grounding of these artists through their works, practices, and writings, this book also locates Japanese experimental arts in an extensive, sustained dialogue with key issues of contemporary critical theory